The Withdrawal of French from the African Sahel: Causes, Consequences, and Future Prospects (2020-2025) (Journal of Human Sciences, 2025)
This study analyzes the withdrawal of French from the African Sahel (Mali, Niger, Burkina Faso, and Chad) between 2020 and 2025, examining its internal and external causes, assessing its impact on regional security and stability, and exploring potential scenarios for France’s return under clear strategic conditions. The study employs a descriptive-analytical methodology and comparative approach across the four countries, utilizing political realism theory and hard and soft power theory to understand international and regional power calculations and the role of military and diplomatic influence. Findings indicate that the withdrawal resulted from complex political, security, and social factors, leading to security vacuums, enhanced local and military influence, and increased significance of international and regional competition, while leaving limited opportunities for a strategic French return.